Implementation of Citizen Relation Management (CRM) applications in the public services of the city of North Jakarta in 2023 - Alifiansyah, Gizka Abrar; Zain, Herlina Muzanah (ARISTO, 2025)
Public service is a form of activity to fulfill the demands of the served party, namely the community by the serving party, namely the state, which in this case is the government. The increasingly strong globalization accompanied by increasingly sophisticated technological developments forces almost all sectors to follow its development, including public services. Modern and internet-based public services are considered as the government's participation in presenting a form of community service that is in accordance with the times. Citizen Relation Management (CRM) is a form of public service innovation that follows technological developments. Citizen Relation Management (CRM) is an application used as a forum for complaints about problems for the people of DKI Jakarta Province which is connected to 13 complaint channels, some of which can be accessed via cellphone using the internet. This study aims to describe how the implementation of the implementation of Citizen Relation Management (CRM) in public services in North Jakarta in 2023. This research methodology uses a qualitative descriptive method with data collection, namely through documentation, observation, and interviews. The data obtained is then analyzed using the theory of 5 (five) criteria for successful implementation. The results showed that the people of North Jakarta felt that the implementation of Citizen Relation Management (CRM) was very helpful and made it easier for them to complain about a problem because of the availability of various complaint channels, some of which could be accessed directly via cellphone. However, during its implementation in 2023 there were still several obstacles, both from internal officers and from the external community itself.